(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Childhood asthma is a complex disorder in which many environmental and personal factors play a role. However, the contribution of these factors to asthma severity is poorly understood. This study aims to determine the relationship between environmental exposures, personal factors and asthma severity among asthmatic children. Methods: This cross-sectional hospital based study was conducted on 180 asthmatic children; they were divided into mild, moderate and severe asthma according to forced expiratory volume in first second. Environmental factors (indoor and outdoor), food allergy, history of other allergic diseases, family history of allergic disorders, time trend of attacks as well as asthma outcome were reported. Results: Children with severe asthma were younger than those with mild or moderate asthma. Severe asthma was significantly linked to family history of allergy, presence of co-morbid allergic diseases, fish, egg and milk allergy, as well as exposure to passive smoking (73.7%) and poor housing conditions. Also, it was significantly linked to presence of unauthorized factories in residential area (31.6 %, p=0.001). As well as, contact with pets (42.1%). Children with severe asthma had more limitations of physical activities (73.7%), missed school days (81.5%), with poor school performance (p=0.04) than those with mild moderate or asthma. Conclusion: Severe asthma was linked to female gender and younger age, co-morbid allergic diseases, family history of atopy and food allergy. It was higher among children residing in places with unauthorized factories and living in substandard housing condition. Children with severe asthma had poor asthma outcome.